Fishery of the Uçá Crab Ucides Cordatus (Linnaeus, 1763) in a Mangrove Area in Cananéia, State of São Paulo, Brazil: Fishery Performance, Exploitation Patterns and Factors Affecting the Catches - Duarte, Luis Felipe De Almeida [UNESP]; Duran, Ricardo Santos [UNESP]; Mendonça, Jocemar Tomasino; Pinheiro, Marcelo Antonio Amaro [UNESP] (Universidade de São Paulo, Instituto Oceanográfico, 2014)
The fishery of the mangrove crab (Ucides cordatus) is one of the oldest sources of food, income and extractive activity in the estuarine systems of Brazil. The state of São Paulo has the largest population of any Brazilian state, and the city of Cananéia, in the Brazilian southeast has the highest recorded level of exploitation of the uçá-crab. Since 1990, this species has been under intense exploitation pressure due to the unauthorized use of a type of trap called 'redinha'. This type of fishing gear is considered harmful and is prohibited by Brazilian law, although its use is very common throughout the country. This study aims to evaluate the exploitation patterns of U. cordatus based on landing data and monitoring of the crab fishermen to verify the population structure of the crab stock and to identify the factors that influence the catches. A general view of the sustainability of the fishery for this resource is also provided for five defined mangrove sectors (areas A to E) at Cananéia. For this purpose, fishery data were recorded during 2009-2010 by the Instituto de Pesca (APTA/SAA-SP), and monitoring of the capture procedures used by two fishermen was conducted to obtain biometry data (CW, carapace width) and gender data for the captured crabs. The redinha trap was very efficient (86.4%) and produced sustainable catches because the trapped crabs were legal-sized males (CW>60 mm), although some traps are lost or remain in the mangrove swamps and can cause pollution by introducing plastic debris. The fishery data were evaluated with a General Linear Model (GLM) based on six factors: the characteristics of the crab fishermen, the time of capture (by month and year), the lunar phase, the productive sector and the reproductive period. The individual crab fishermen's empirical knowledge, the year of capture and the productive sector were the strongest influences on the crab catch per unit effort (CPUE). Differing extraction patterns were found in the five sectors examined in the Cananéia estuary. These findings underscore the need for a reassessment of the prohibition of the trap's use, raising discussion as to its possible construction with biodegradable materials, thus ensuring profitable and sustainable catches through a local participatory management process.

A pesca do caranguejo-uçá (Ucides cordatus) é uma das mais antigas atividades extrativas para a obtenção de fonte de alimento e renda nos sistemas estuarinos do Brasil. O Estado de São Paulo é o mais populoso e a cidade de Cananéia, localizada no sudeste, tem o maior volume registrado de captura do caranguejo-uçá para a região. Desde 1990, esta espécie vem sofrendo intensa pressão pesqueira pelo uso indiscriminado de um tipo de armadilha conhecida como "redinha". Este tipo de arte de pesca é considerado uma ameaça à população do caranguejo, sendo proibido pela legislação brasileira, embora seu uso seja comum em todo o país. Este estudo teve como objetivo avaliar os padrões de exploração de U. cordatus com base em dados de desembarque, bem como do monitoramento das capturas pelos catadores, com o intuito de verificar a estrutura populacional do estoque e identificar os fatores que vêm influenciando os rendimentos pesqueiros da espécie. Uma visão geral da sustentabilidade pesqueira foi também elaborada para cinco setores de pesca estabelecidos (áreas de A a E) em Cananéia. Para este propósito, dados sobre as pescarias foram registrados durante 2009-2010 pelo Instituto de Pesca (APTA/SAA-SP), bem como o acompanhamento das capturas de dois pescadores foi realizado para se obter dados de biometria (CW, largura da carapaça) e gênero dos animais capturados. Embora algumas armadilhas tenham sido perdidas/deixadas nos manguezais, promovendo certa poluição pela introdução desses detritos plásticos, estas foram consideradas eficientes (86,4%) na captura do caranguejo-uçá, bem como corretas como instrumento de captura, uma vez que 100% dos espécimes por elas capturados eram machos com tamanho acima daquele permitido por lei (CW > 60 mm). Os dados sobre as pescarias foram avaliados utilizando-se o modelo geral linearizado (MGL), com base em seis fatores explicativos: os diferentes pescadores, o período de captura (por mês e ano), a fase lunar, o setor produtivo e o período reprodutivo. O conhecimento empírico dos pescadores de caranguejo, o ano da captura e do setor produtivo foram os principais fatores explicadores da variabilidade na captura de caranguejo por unidade de esforço (CPUE). Diferentes padrões de exploração foram observados nos cinco setores analisados no estuário de Cananéia. Os resultados obtidos ressaltam a necessidade de uma reavaliação na proibição do uso da armadilha "redinha", abrindo discussão sobre sua confecção com materiais biodegradáveis, assegurando, assim, capturas rentáveis e sustentáveis por meio de uma gestão participativa local.
Keywords: CPUE; Modelo Geral Linearizado; Padrões de explotação; Manguezal; Ucides cordatus.; CPUE; General Linear Model; Exploitation pattern; Mangrove; Ucides cordatus.